Grammar Learning At Tertiary Level In Indonesia: A Curriculum Development Of Genre-Task Based Approach - Surasmi, Wuwuh Asrining; Suparti, Suparti; Fadilah, Eka (Universitas Malikussaleh, 2020)
This article explores the grammar learning in two influential English language teaching (ELT) curriculum approaches to tertiary level and the potential approach to interweave them. The two prominent approaches shaping language learning in Indonesia are communicative language teaching (CLT) specified in Task-based Instruction and Genre approaches rooted in Systemic Functional Language (SFL). Given the various curriculum which comes and goes, bringing together with miscellaneous methods or approaches, it is urgently needed to adapt rather than adopt the wholesale methods or approaches by making the nexus between those two aproaches to fit the context. This article aims at revisiting creative and innovative grammar teaching and learning at tertiary educational level. We elucidate how those approaches foster English as a Foreign Language (EFL), notably, how grammar should be learnt and assessed through them.